2013
DOI: 10.1021/nn4045276
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Nanotube Core Graphitic Shell Hybrid Fibers

Abstract: A carbon nanotube yarn core graphitic shell hybrid fiber was fabricated via facile heat treatment of epoxy-based negative photoresist (SU-8) on carbon nanotube yarn. The effective encapsulation of carbon nanotube yarn in carbon fiber and a glassy carbon outer shell determines their physical properties. The higher electrical conductivity (than carbon fiber) of the carbon nanotube yarn overcomes the drawbacks of carbon fiber/glassy carbon, and the better properties (than carbon nanotubes) of the carbon fiber/gla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…The important vibration bands are marked in Figure A . 3D SWCNT shows an enhanced and broadened D band, indicating the enhancement in the out-of-plane bending mode induced D-band phonon .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The important vibration bands are marked in Figure A . 3D SWCNT shows an enhanced and broadened D band, indicating the enhancement in the out-of-plane bending mode induced D-band phonon .…”
Section: Resultsmentioning
confidence: 99%
“…The important vibration bands are marked in Figure 2A. 25 3D SWCNT shows an enhanced and broadened D band, indicating the enhancement in the out-of-plane bending mode induced D-band phonon. 26 The MWCNTs have considerable D-band in the pristine form itself, and the 3D MWCNT did not show a considerable change in the D band phonon; however, a drastic change in the 2D band is observed, indicating the roles of induced defects upon functionalization and coupling.…”
Section: Acs Catalysismentioning
confidence: 99%
“…These systems could be useful in a series of devices, such as electronics, photovoltaics, and optoelectronic. In addition, two different hybridized fullerene-graphene composites (Figure 13), (a) C 60 fullerenes physisorbed on a monolayer of graphene and (b) graphene nanoribbons functionalized using different-sized fullerene molecules such as C 20 , C 60 , C 70 , and C 60 derivative PCMB ( [6,6]-phenyl-C61-butyric acid methyl ester), were DFT-studied. 42 It was revealed that the C 60 adsorbed on a graphene layer is not subjected to changing its low energy states.…”
Section: Industrial and Engineering Chemistry Researchmentioning
confidence: 99%
“…At the same time, it is known that carbon allotropes can form their composites or hybrids because of the spontaneous formation of covalent or van der Waals bonds between carbon atoms, initially belonging to the precursors. A certain number of reports are dedicated to combinations of carbon nanostructurized allotropes, as well as graphite/carbon nanoallotrope hybrids, which can be prepared from already formed nanocarbons or in situ from their hydrocarbon precursors as a result of pyrolysis or solvothermal reactions. Thus, produced hybrids can possess unusual properties due to the simultaneous presence of carbon structures of distinct dimensionality and reactivity.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the theoretical description for the thermal conductivity enhancement was ultimately given by Chu as KKm=1+fc(Kceff/Km)/3+2fg(Kgeff/Km)/31(2fc+fg)/3 where K* and K m represent the thermal conductivity of composite and matrix, respectively; f denotes the volume fraction. It was noted that GNP–matrix and CNT–matrix are assumed to have the same R K since the CNT can be treated as a concentrically wrapped‐up GNP . The unknown parameters of R K and l g can then be obtained by back‐calculation from the experimental thermal conductivity of the composites with individual CNT filler and GNP filler, respectively.…”
Section: Resultsmentioning
confidence: 99%